2004
DOI: 10.1023/b:bile.0000019563.92959.0e
|View full text |Cite
|
Sign up to set email alerts
|

Newly isolated bacterial strains belonging to Bacillaceae (Bacillus sp.) and Micrococcaceae accelerate death of the honey bee mite, Varroa destructor (V. jacobsoni), in laboratory assays

Abstract: Newly isolated bacterial strains belonging to Bacillaceae (Bacillus sp.), Micrococcaceae and three unidentified strains were tested for their pathogenicity against the mite, Varroa destructor. The Bacillus sp. strain and two of the strains belonging to the Micrococcaceae family significantly decreased the time for 50% mortality of the mite population (up to 57%) and hence may be potential control agents. In in vitro bioassay whole cells, extracellular broth and cellular extract of the Bacillus sp. strain effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 10 publications
0
16
0
Order By: Relevance
“…and members of Miccrococaceae caused up to 54% mite mortality (Tsagou et al . ). These two groups of acaropathogenic bacteria were not detected in Varroa from winter beehive wax debris in our study; however, we found Pseudomonas as another putative acaropathogenic bacterium.…”
Section: Discussionmentioning
confidence: 97%
“…and members of Miccrococaceae caused up to 54% mite mortality (Tsagou et al . ). These two groups of acaropathogenic bacteria were not detected in Varroa from winter beehive wax debris in our study; however, we found Pseudomonas as another putative acaropathogenic bacterium.…”
Section: Discussionmentioning
confidence: 97%
“…Viruses, bacteria (BT), protozoa, nematodes, rickettsiae Pathogens cause lethal infections on mites Some strains of Bacillaceae and Micrococcaceae increased mortality in in vitro tests; until now no Varroa-specific strains known Aronson et al (1986), Ball and Allen (1988), Glinski and Jarosz (1990), Tsagou et al (2004), Van der Geest et al (2000) P. Rosenkranz et al / Journal of Invertebrate Pathology 103 (2010) S96-S119 S111 natural downfall of 0.5-10 mites on the bottom board is regarded to be the threshold for a basic necessity of treatment (Arbeitsgemeinschaft der Institute für Bienenforschung e.V., 2007; Gregorc and Smodis Skerl, 2007;Liebig, 2001;Martin, 2001b). This corresponds to an absolute mite population of 2000-3000 mites which is considered as an economic threshold (Delaplane and Hood, 1999).…”
Section: Biotechnical and Biological Methodsmentioning
confidence: 99%
“…Dead adult females of V. destructor were collected from the bottom board and some from capped brood of hives not treated with miticides; with the help of a camel hair brush they were taken and placed individually in sterile 1.5 mL microcentrifuge tubes (Tsagou et al 2004). They were then disinfected with 2 % sodium hypochlorite for 10 s and washed twice with sterile water, and placed in microcentrifuge tubes (one mite per tube).…”
Section: Isolation Of Bacteria From Dead Adult Females Of Varroa Destmentioning
confidence: 99%
“…An alternative strategy to control V. destructor is the use of entomopathogenic microorganisms such as bacteria and fungi (Hamiduzzaman et al 2012;Tsagou et al 2004). This new approach meets the growing concern for new methods of pest control that do not pollute and are more environmentally friendly (Lacey et al 2001;Meikle et al 2012).…”
Section: Introductionmentioning
confidence: 99%